2019
DOI: 10.12693/aphyspola.135.1237
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Electrical Conductivity of Ethylene Glycol Containing Indium Oxide Nanoparticles

Abstract: Nanofluids as a quite new group of nanomaterials are very promising. A great potential of nanofluids was noted in second half of twentieth century and it was related with high increase of thermal conductivity. The most favourable effects of using nanofluids can be achieved in heat transfer systems, but also in other branch of industry like car, energy, and mining industry, even biomedicine industry. This paper presents results of experimental investigation of electrical conductivity of nanosuspension containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Anyhow, most of the researchers (see [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]) have explained the increase in electrical conductivity mainly by EDL formation; that is, the structure of charge accumulation and charge separation that always occurs at the interface when an electrode (in this case solid nanoparticles) is immersed into an electrolyte solution (i.e., the base fluid).…”
Section: Discussion On Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anyhow, most of the researchers (see [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]) have explained the increase in electrical conductivity mainly by EDL formation; that is, the structure of charge accumulation and charge separation that always occurs at the interface when an electrode (in this case solid nanoparticles) is immersed into an electrolyte solution (i.e., the base fluid).…”
Section: Discussion On Experimental Resultsmentioning
confidence: 99%
“…Studies on temperature variation influence over electrical conductivity are summarized in Table 3. The overall conclusion was that the temperature increase leads to a linear increase in the electrical conductivity [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57] which is a logical phenomenon with major occurrence in the physics of suspensions. Some details are already presented in both Table 1 and Section 3 and a discussion will be undertaken below.…”
Section: Discussion On Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The In 2 O 3 nanoparticles used are in the form of a dry, light yellow powder. The average size of the indium oxide nanoparticles as declared by the manufacturer is 4 nm and was confirmed using a JEOL JSM-6700F field emission scanning electron microscope (SEM) (JEOL, Tokyo, Japan), and the images taken on it can be found elsewhere [21].…”
Section: Nanoparticle Characterisationmentioning
confidence: 97%
“…In the literature, there are just a few papers on selected properties of indium oxide nanofluids in ethylene glycol (In 2 O 3 -EG). One of these is the work of Fal et al [21] in which they found an increase in the electrical conductivity of these nanofluids with both concentration and temperature. The maximum increase in electrical conductivity of In 2 O 3 -EG nanofluids, 27 300% was detected for a volume fraction of 0.0081 at 333.15 K. Żyła et al [22] presented the results of an experimental study of the dynamic viscosity of indium oxide nanofluids in ethylene glycol and found that these materials exhibit Newtonian character for each nanoparticle fraction tested.…”
mentioning
confidence: 99%